2018
DOI: 10.1002/mabi.201800335
|View full text |Cite
|
Sign up to set email alerts
|

Nanoimprinted Anisotropic Topography Preferentially Guides Axons and Enhances Nerve Regeneration

Abstract: Surface topography has a profound effect on the development of the nervous system, such as neuronal differentiation and morphogenesis. While the interaction of neurons and the surface topography of their local environment is well characterized, the neuron–topography interaction during the regeneration process remains largely unknown. To address this question, an anisotropic surface topography resembling linear grooves made from poly(ethylene‐vinyl acetate) (EVA), a soft and biocompatible polymer, using nanoimp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 58 publications
1
23
0
Order By: Relevance
“…PDMS serves as a negative mold after polymer casting and curing in micromolding and microtransfering. Some studies also used nanoimprinting lithography to prepare grooves in nano size to direct axon growth [ 102 ].
Fig.
…”
Section: Anisotropic Surface Patternsmentioning
confidence: 99%
See 1 more Smart Citation
“…PDMS serves as a negative mold after polymer casting and curing in micromolding and microtransfering. Some studies also used nanoimprinting lithography to prepare grooves in nano size to direct axon growth [ 102 ].
Fig.
…”
Section: Anisotropic Surface Patternsmentioning
confidence: 99%
“…During peripheral nerve regeneration, axons need to navigate to reach the distal segment, where Wallerian degeneration occurs. To match the diameter of axons (0.05–1.25 μm) without myelinating cells under injured conditions, Huang et al used nanoimprinting to engineer parallel grooves on a poly (ethylene-co-vinyl acetate) (PEVA) copolymer surface [ 102 ]. Both peripheral neurons from DRG and cortical neurons survived and aligned within the grooves.…”
Section: Anisotropic Surface Patternsmentioning
confidence: 99%
“…This alignment induces cell migration and organization along the nerve on a preferred direction, from the proximal to the distal stump (Huang Y.-A. et al, 2018). With intensive research in this field, it is now known that aligned topographical cues enhanced neurite outgrowth by activating mTOR pathway (Thomson et al, 2017).…”
Section: Tissue Engineering and Regenerative Medicine Concepts For Pnrmentioning
confidence: 99%
“…Huang Y.-A. et al (2018) reported that they were able to exactly place the neuronal cell body and control the direction of axonal growth by merging surface topography and a cell placement device technologies, creating the prospect of engineering complex tissues. Furthermore, they were able to create an on-site axotomy, studying how the topography can influence the initial regeneration of injured axons.…”
Section: Tissue Engineering and Regenerative Medicine Concepts For Pnrmentioning
confidence: 99%
“…nanodiamonds (NDs), beads, and others (Brunetti et al, 2010;Cyster et al, 2004;Edgington et al, 2013;Huang et al, 2014;Kang et al, 2012b;Kang et al, 2014;Khan et al, 2005;Thalhammer et al, 2010)], anisotropic pattern [e.g. ridges, grooves, gratings, and electrospun fibers (Baranes et al, 2012;Clark et al, 1991;Huang et al, 2018;Johansson et al, 2006;Kang et al, 2012a;Kang et al, 2011;Nagata et al, 1993;Nikkhah et al, 2012;Patel et al, 2007;Rajnicek and McCaig, 1997;Schnell et al, 2007;Tonazzini et al, 2014;Webb et al, 1995;Xie et al, 2009;Yang et al, 2005)], and isotropic pattern [e.g. pillars, nanotubes, and columns (Dowell-Mesfin et al, 2004;Hanson et al, 2009;Hu et al, 2004;Mattson et al, 2000;Park et al, 2016;Roberts et al, 2014;Xie et al, 2010)].…”
Section: Introductionmentioning
confidence: 99%